PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN BUMN YANG TERDAFTAR DI BEI PERIODE 2007-2021 - Fitriana, Anita Noni; Juwita, Ratna (JURNAL LENTERA AKUNTANSI, 2023)
Financial performance is an important instrument used to determine whether a company is in health conditions or not. The way to measure financial performance is to look at profitability ratios through ROA and market ratios through EPS. The purpose of this research are to obtain empirical evidence regarding the influence of CSR and GCG on the financial performance of government banking as measured using ROA and EPS. This study uses secondary data, the population used are government banking companies listed on the Indonesia Stock Exchange in 2007-2021. The sample selection used a purposive sampling method and obtained 60 observational data. The analytical method in this study used panel data regression analysis which was processed using Eviews version 12 with the random effect model method for the ROA ratio and the fixed effect model for the EPS ratio. The results of this study indicate that CSR and GCG as measured through independent board have a significant effect on the financial performance of government banking, then GCG as measured using an audit committee has a significant effect on financial performance as measured by EPS, then the audit committee on ROA and institutional ownership does not significant effect on financial performance as measured by ROA and EPS.Keywords: CSR, GCG, Audit Committee, Independent Board, Institutional Ownership, ROA, EPS